The Protection of Genomic Data in Italy in the Specific Case of Forensic DNA Phenotyping: Regulatory Prospects (BioLaw Journal - Rivista di BioDiritto, 2026)
The paper explores the use of Forensic DNA Phenotyping (FDP) in Italy and the EU, an investigative technique that infers physical characteristics from biological traces. It highlights how FDP raises significant concerns regarding the protection of genetic data and the risk of discrimination. The relevant legislation is examined to underline the potential violation of privacy and the lack of a specific regulatory framework governing its use and providing adequate safeguards. The paper also assesses the impact of artificial intelligence in support of FDP, warning of an amplification of the associated risks. Suggestions are put forward to balance public security with the right to personal data protection.
Keywords: forensic DNA phenotyping; genomic data protection; proportionality principle; artificial intelligence; privacy